Main positions of V&V procedure for the softwares used at reactor pressure vessel dosimetry - V. N. Bukanov; V. L. Dyemokhin; I. I. Lipsky (Ядерна фізика та енергетика)
Modern approaches to V&V procedure of software are considered and analyzed. It is shown that V&V procedure should include three stages: qualification, verification and validation. Main positions of V&V procedure for the software to be a component of VVER pressure vessel irradiation conditions determination technique are worked out.